PENGARUH INOVASI PRODUK DAN ORIENTASI PASAR TERHADAP KINERJA PEMASARAN PADA PT ASURANSI PRUDENTIAL SYARIAH KOTA MEDAN - Armando Nasution; Nurwani; Imsar (POLITEKNIK LP3I JAKARTA, 2025)
The aim of this research is to determine the influence of product innovation and market orientation variables on improving the marketing performance of PT. Prudential Sharia Insurance Medan Branch. The type of research used by the author is quantitative descriptive. The results of this research are that the product innovation variable on increasing marketing performance shows that the calculated t is greater than the t table. This can be interpreted as saying that product innovation has an effect on marketing performance, and so H1 is accepted. This can mean that there is a significant influence between product innovation and marketing performance. The market orientation variable on marketing performance shows that t is greater than t. Table H2 is accepted. This can be interpreted as market orientation influencing marketing performance. Based on table 5, the calculated F value is greater than table F, so H4 is accepted. It can be concluded that the independent variables, namely product innovation and market orientation, simultaneously influence the dependent variable, namely marketing performance.